Preschool children’s prejudices: A phenomenological study - Çelik, Meryem Nur; Şahin-Sak, İkbal Tuba (Erken Çocukluk Çalışmaları Dergisi, 2019)
Data for this phenomenological study of preschoolers’ prejudices were collected through an interview protocol developed by the researchers. The participants, selected using purposeful sampling, were 100 four- to six-year-old children from Van, Turkey. For data analysis, coders looked firstly at word or phrase repetition, and then at the connectors the children used. This revealed that the children had several distinct prejudices related to each of seven main themes drawn from the existing literature: (1) race, (2) age, (3) physical abilities, (4) physical characteristics, (5) economic class, (6) gender and (7) family composition. However, some of the children’s prejudices were nested and interrelated. For instance, when expressing prejudices related to age, they tended to exhibit their prejudices related to gender or physical characteristics.